Low prevalence of ataxic polyneuropathy in a community with high exposure to cyanide from cassava foods - Oluwole, O.S.; Onabolu, O.A.; Cotgreave, I.A.; Rosling, H.; Persson, Anna S.; Link, H. (Springer, 2002)
Ataxic polyneuropathy, which occurs in endemic form in an area in southwest Nigeria, is attributed to exposure to cyanide from cassava foods. Exposure to cyanide from cassava is, however, not exclusive to this endemic area. In this study, the occurrence of ataxic polyneuropathy was compared in two communities in Nigeria, one located in the endemic area and the other located outside the endemic area. Both communities have been shown to have high exposure to cyanide from cassava foods. The prevalence of ataxic polyneuropathy in Jobele, Nigeria, a community located outside the endemic area, was compared with the prevalence of ataxic polyneuropathy in Ososa, Nigeria, a reference community located in the endemic area. Subjects aged 10 years and above in both communities were screened for ataxic polyneuropathy. Ataxic polyneuropathy was diagnosed if sensory gait ataxia and sensory polyneuropathy were present. The intake of cassava foods, biomarkers of exposure to cyanide, and intake of protein and sulphur were measured. Prevalence of ataxic polyneuropathy were 490 per 10,000 in Ososa, and 17 per 10,000 in Jobele. The age-adjusted prevalence ratio is 4 (95% CI 0-9). The mean intake of all cassava foods in Jobele was 7 meals/person/week (95% CI 6-8), while the mean intake of all cassava foods in Ososa was 10 meals/person/week (95 % CI 9-11). The concentration of thiocyanate in the plasma was above the reference limit in 65% (95% CI 57-73) in Jobele, and 40 % (95% CI 27-52) in Ososa. The intake of protein was significantly lower in Ososa than in Jobele, but the concentrations of glutathione, cysteine and gamma-glutamylcysteine in the plasma were within the same range in Jobele and Ososa. This study shows that the occurrence of ataxic polyneuropathy is low in a community where exposure to cyanide is high. This suggests that exposure to cyanide is not a direct cause of ataxic polyneuropathy.